In vivo evidence for reduced ion channel expression in motor axons of patients with amyotrophic lateral sclerosis. (17th October 2018) - Howells, James; Matamala, José Manuel; Park, Susanna B.; Garg, Nidhi; Vucic, Steve; Bostock, Hugh; Burke, David; Kiernan, Matthew C.
Abstract : Key points: The progressive loss of motor units in amyotrophic lateral sclerosis (ALS) is initially compensated for by the reinnervation of denervated muscle fibres by surviving motor axons. A disruption in protein homeostasis is thought to play a critical role in the pathogenesis of ALS. The changes in surviving motor neurons were studied by comparing the nerve excitability properties of moderately and severely affected single motor axons from patients with ALS with those from single motor axons in control subjects. A mathematical model indicated that approximately 99% of the differences between the ALS and control units could be explained by a non‐selective reduction in the expression of all ion channels. These changes in ALS patients are best explained by a failure in the supply of ion channel and other membrane proteins from the diseased motor neuron. Abstract: Amyotrophic lateral sclerosis (ALS) is characterised by a progressive loss of motor units and the reinnervation of denervated muscle fibres by surviving motor axons. This reinnervation preserves muscle function until symptom onset, when some 60–80% of motor units have been lost. We have studied the changes in surviving motor neurons by comparing the nerve excitability properties of 31 single motor axons from patients with ALS with those from 21 single motor axons in control subjects. ALS motor axons were classified as coming from moderately or severely affected muscles according to the compound muscle action potential amplitude of the parent muscle. Compared with control units, thresholds were increased, and there was reduced inward and outward rectification and greater superexcitability following a conditioning impulse. These abnormalities were greater in axons from severely affected muscles, and were correlated with loss of fine motor skills. A mathematical model indicated that 99.1% of the differences between the moderately affected ALS and control units could be explained by a reduction in the expression of all ion channels. For the severely affected units, modelling required, in addition, an increase in the current leak through and under the myelin sheath. This might be expected if the anchoring proteins responsible for the paranodal seal were reduced. We conclude that changes in axonal excitability identified in ALS patients are best explained by a failure in the supply of ion channel and other membrane proteins from the diseased motor neuron, a conclusion consistent with recent animal and in vitro human data. Key points: The progressive loss of motor units in amyotrophic lateral sclerosis (ALS) is initially compensated for by the reinnervation of denervated muscle fibres by surviving motor axons. A disruption in protein homeostasis is thought to play a critical role in the pathogenesis of ALS. The changes in surviving motor neurons were studied by comparing the nerve excitability properties of moderately and severely affected single motor axons from patients with ALS with those from single motor axons in control subjects. A mathematical model indicated that approximately 99% of the differences between the ALS and control units could be explained by a non‐selective reduction in the expression of all ion channels. These changes in ALS patients are best explained by a failure in the supply of ion channel and other membrane proteins from the diseased motor neuron.